1999
DOI: 10.1016/s0741-5214(99)70074-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgery after failed percutaneous renal artery angioplasty

Abstract: Operative repair after F-PTRA was altered in 59% of the patients with atherosclerosis and in 68% of patients with FMD. Blood pressure benefit for patients with FMD was unchanged after F-PTRA. However, the blood pressure benefit was significantly decreased among patients with atherosclerosis. Decreased EGFR after F-PTRA was recovered with operative renal artery repair. However, postoperative EGFR as compared with EGFR prior to PTRA was unchanged. Blood pressure and renal function response after F-PTRA for ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…Renal function in atherosclerotic RAS pretreated by PTRA did not improve as well as in non-atherosclerotic patients [13,14]. This is in agreement with our own findings: in atherosclerotic RAS we found a stabilization of eGFR, whereas in patients with FMD, there was no deterioration of the average normal eGFR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Renal function in atherosclerotic RAS pretreated by PTRA did not improve as well as in non-atherosclerotic patients [13,14]. This is in agreement with our own findings: in atherosclerotic RAS we found a stabilization of eGFR, whereas in patients with FMD, there was no deterioration of the average normal eGFR.…”
Section: Discussionsupporting
confidence: 92%
“…In atherosclerotic RAS, Wong et al showed cure of hypertension in 7%, improvement in 50% and unchanged hypertension in 43% of all patients (n=28) [14]. Lacombe and Ricco report similar results with improvement in 53% and unchanged hypertension in 43% (n=17) [13].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The technical results of PTRA in adults range from 47% to 90% [1,8,10,24,25]. Ostial arteriosclerotic stenosis show disappointing success rates from 24% to 35%.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to cross the lesion with a guidewire/balloon may be one reason for the primary failure rate [2,11,24,31]. Lesions resistant to dilatation with balloon inflation to 6 atm pressure can be treated using high-pressure balloons [6,14].…”
Section: Discussionmentioning
confidence: 99%